cGAS-like receptors drive a systemic STING-dependent host response in Drosophila - Xianlong Ai; Huimin Deng; Xiaoyan Li; Ziming Wei; Yuqiang Chen; Ting Yin; Junhui Zhang; Jingxian Huang; Haoming Li; Xiaoqing Lin; Long Tan; Di Chen; et al. (Cell Reports)
Summary: cGAS-like receptor (cGLR)-stimulator of interferon genes (STING) recently emerged as an important pathway controlling viral infections in invertebrates. However, its exact contribution at the organismal level remains uncharacterized. Here, we use STING::GFP knockin reporter Drosophila flies to document activation of the pathway in vivo. Four tissues strongly respond to injection of the cyclic dinucleotide 3′2′- cyclic guanosine monophosphate-adenosine monophosphate (cGAMP): the central nervous system, midgut, Malpighian tubules, and genital ducts. The pattern of STING::GFP induction in flies injected with 3′2′-cGAMP or infected by two viruses with different tropism suggests that the reporter is induced by a systemic signal produced in virus-infected cells. Accordingly, ectopic expression of cGLR2 in the fat body induces STING signaling in remote tissues and a cGLR1/2-dependent activity is transferred to females during mating. Furthermore, viral infection can alter sleep in a cGLR1/2- and STING-dependent manner. Altogether, our results reveal a contribution of cyclic dinucleotide signaling to a systemic host response to viral infection in Drosophila.